MASTECH (MASTITIS DETECTION TECHNOLOGY) METODE DETEKSI MASTITIS BERBASIS BIOSURFAKTAN ASAL Pseudomonas sp - Pratomo, Faizal Agung; Zobda, Paura Rangga; Shanda, Farras; Wildan, Muhamad; Putra, Dimas Rizky Eerste (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Today, the needs of milk in Indonesia is increasing, while in terms of quality canât meet national needs. One reason is mastitis disease. Mastitis is inflammation of udder that marked changes in physical and chemical milk with or without pathological of the mammary gland. Mastitis detection currently used is California Mastitis Test (CMT), CMT weakness is expensive and use of chemicals. so that, necessary new methods, one of which uses biosurfactants. The advantages of using biosurfactants are environment receiving, as biodegradable and non-toxic. Biosurfactants have potential in management and protection of the environment, so it could be mastitis detection tool.Â Keywords: Milk, mastitis, CMT, biosufactants, Pseudomonas sp.